Incentives, conditionality and collective action in payment for environmental services - Kerr, John; Vardhan, Mamta; Jindal, Rohit (My University, 2014)
As payment for environmental services (PES) initiatives spread to collectively managed natural resources, questions arise because the incentive structures that might be appropriate for individually managed resources will not necessarily promote the collective action required to manage the commons. Theory suggests challenges for cash payments to promote collective action, and for alternative payment types to facilitate conditionality. Possible ways to reconcile this disconnect involve conceiving of PES more broadly through the use of multiple forms of payment including non-cash incentives and placing greater focus on building institutions for collective action than on strict conditionality.
Keywords: commons; collective action; conditionality; Indonesia; Mexico; payment for ecosystem services; payment for environmental services